Preliminary Observations on Information Technology Needs and Priorities for the Centers for Medicare and Medicaid Services : an Interim Report. (National Academies Press, 2010)
Increasingly, the core mission of the Centers for Medicare and Medicaid Services (CMS), an agency of the Department of Health and Human Services, is expanding from one of focusing on prompt claims payment to one of becoming more broadly involved in improving health care quality and efficiency. The requirements for the information technology (IT) systems of CMS are changing as its mission changes, and the efforts to evolve its systems from those designed to support the agency's historical mission come in the midst of a push to modernize the nation's health care IT more broadly. These new challenges arise even as CMS must meet challenging day-to-day operational requirements and make frequent adjustments to its business processes, code, databases, and systems in response to changing statutory, regulatory, and policy requirements. In light of these and other emerging challenges, CMS asked the National Research Council to conduct a study that would lay out a forward-looking vision for the Centers for Medicare and Medicaid Services, taking account of CMS's mission, business processes, and information technology requirements. The study is being conducted in two phases. The first, resulting in the present volume, draws on a series of teleconferences, briefings, and an information-gathering workshop held in Washington, D.C., on September 27-28, 2010. The second phase, drawing on that workshop and on additional briefings, site visits, and committee deliberations, will result in a final report with recommendations, to be issued at the end of the project in 2011.